ZnO-beta zeolite mediated simple and efficient method for the one-pot synthesis of quinoxaline derivatives at room temperature - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2010)
A rapid and an efficient one-pot method for the synthesis of quinoxalines catalysed by ZnO-beta zeolite at room temperature is described. This environmentally benign method provides several advantages over methods that are currently employed such as a simple work-up, mild reaction conditions, good to excellent yields, and a process to recover and reuse the catalyst for several cycles with consistent activity.
Keywords: cyclocondensation; Quinoxaline; Room temperature; ZnO-beta zeolite